Attitudes and expectations of patients on home parenteral nutrition towards eHealth: A multicenter survey. (December 2022) - Schönenberger, Katja A.; Reber, Emilie; Vu, Duy-Tan; Krieger-Grübel, Claudia; Gerber, Philipp A.; Muri, Raphaela; Huwiler, Valentina V.; Mühlebach, Stefan; Leuenberger, Michèle; Stanga, Zeno
Summary: Background & aims: Advances in technology enable patients on home parenteral nutrition (HPN) to manage their treatment more independently and safely. eHealth is a promising application of electronic means in healthcare, aimed at improving and simplifying processes and connecting the different parties involved. A thorough understanding of the attitudes and expectations of patients on HPN towards eHealth is a prerequisite for a successful implementation. However, to the best of our knowledge, such a survey preceding the implementation of HPN specific eHealth care has never been conducted. The objective of this preliminary survey is the acquisition of insights on the attitudes and expectations of patients on HPN towards eHealth. Resulting findings then serve as the basis for the design of an eHealth platform to facilitate communication among those involved in HPN care, improve the HPN management, and safeguard and monitor the treatment. Methods: We conducted a survey on the attitudes and expectations of patients towards an envisioned eHealth platform for HPN. Patients were recruited from large Swiss hospitals by their treating physician or directly by the research team. The surveys were conducted between September 2020 and October 2021 by structured personal interviews based on a questionnaire. Results: We included 35 patients on HPN (21 [60%] females) treated in ambulant care of 4 hospitals. They had a median (interquartile range) age of 55 (18) years and a median (interquartile range) duration of parenteral nutrition of 1.3 (3.1) years. Most patients (n = 30, 86%) were equipped with a smartphone, tablet, or computer and 22 (63%) used apps and rated themselves as proficient with the corresponding digital device. A majority of patients rated the following aspects and features of the platform as important: Data collection and storage (n = 29, 83%), checklists for PN, catheter, and infusion pump handling (n = 28, 80%), video instructions (n = 27, 77%), and videoconferencing with physicians (n = 25, 71%). Most patients (n = 26, 74%) were willing to enter data into the platform themselves. The type of data to be entered should be defined on an individual basis. Conclusions: Patients on HPN are open to videoconference consultations and using an eHealth platform. Two-thirds have the necessary technical skills including suitable digital devices for an eHealth care. We identified key features of an eHealth platform to improve HPN management.